Сказки дедушки Иринея: [для младшего школьного возраста] / В. Ф. Одоевский - Одоевский Владимир Федорович (Логосвос, 2020)
Экземпляры: БС (20200715) / Инвентарный номер: РТШ54917 / Цена: / Сис.шифр: 84(2) / Авт.знак: О-44 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)-4